Concise and highly stereoselective syntheses of d-fagomine and 2-epi-fagomine. Issue 12 (23rd March 2016) - Kallam, Srinivasa Reddy; Datrika, Rajender; Khobare, Sandip R.; Gajare, Vikas S.; Rajana, Nagaraju; Mohan, H. Rama; Babu, J. Moses; Siddaiah, V.; Pratap, T.V.
Graphical abstract: Abstract: Highly stereoselective total syntheses of polyhydroxylated piperidinesd -fagomine and 2- epi -fagomine have been developed starting from 3, 4, 6-tri- O -benzyl-d -glucal which is a derivative ofd -Glucose. Key steps in the synthesis of these azasugars involved N -Boc-protected amine preparation from oxime followed by stereo specific iodination of alcohol and cascade cyclization triggered by N -Boc deprotection.